ISTILAH KEKERABATAN DALAM BAHASA INGGRIS DAN BAHASA MORI (SUATU ANALASIS KONSTRASTIF) - Arikalang, Christy Natasha; Pelealu, Hetty; Pamantung, Rina P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research attempts to describe and analyze the kinship terms of English and Mori Language (Analysis Contrastive). English and Mori language are two different groups of language which have specific patterns of kinship terminologies. Both languages have a special set of terms to indicate the kinship relations. This research aims to compare and contrast the analysis between English and Mori Language and using Ladoâ€™s (1957) concept as well as using descriptive method by Burling (1971) in which the kinship terms are characterized as â€œconsanguinalâ€ and â€œafinal.â€ The writer also used the method of Wardaugh, Burling and Loundsburry quoted in Leech to find out the similarities and differences between the languages. The data of English were collected from several relevant text books, and severalreliable sources from the internet, and the data of Mori Language were collected from informants through interview. The result of this research shows that both English and Mori Language have similarities in terms of sex, generation and lineage. The difference is that the English kinship terms give distinctions on the sex of all the relatives of in ego, while Morilanguage only has on severalrelatives of in ego. In generation, both of this languages have same generation such as four generations above and below ego.Keywords: Kinship terms of English and Mori Language, Contrastive Analysis.